2010
DOI: 10.1007/s11661-010-0211-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron Precipitation Behavior on the Hot Ductility of Boron Containing Steel

Abstract: The effect of boron (B) precipitation behavior on the hot ductility of B containing steel was investigated. Hot ductility of B containing steel was sensitive to the cooling rate (CR) in the range of 1 to 20 K/s (1 to 20°C/s), whereas that of B-free steel showed little change with CR. Increased CR causes deepening and widening of the ductility trough in B containing steel. Particle tracking autoradiography (PTA) analysis and transmission electron microscope (TEM) image of the samples show that boron nitride (BN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…The hot ductility of the B containing steel was found to be sensitive to the cooling rate in the range of 1 to 20 o C/s, whereas that of B-free steel showed little change with cooling rate. Increased cooling rate causes deepening and widening of the ductility trough in B containing steel as shown Fig.2.56 [146]. Particle tracking autoradiography (PTA) analysis and transmission electron microscope (TEM) images of the samples showed that BN particles formed along prior austenite grain boundaries, and that as cooling rate increases, these particles become smaller and more numerous as shown Fig.2.57 [146].…”
Section: Boronmentioning
confidence: 94%
See 2 more Smart Citations
“…The hot ductility of the B containing steel was found to be sensitive to the cooling rate in the range of 1 to 20 o C/s, whereas that of B-free steel showed little change with cooling rate. Increased cooling rate causes deepening and widening of the ductility trough in B containing steel as shown Fig.2.56 [146]. Particle tracking autoradiography (PTA) analysis and transmission electron microscope (TEM) images of the samples showed that BN particles formed along prior austenite grain boundaries, and that as cooling rate increases, these particles become smaller and more numerous as shown Fig.2.57 [146].…”
Section: Boronmentioning
confidence: 94%
“…Increased cooling rate causes deepening and widening of the ductility trough in B containing steel as shown Fig.2.56 [146]. Particle tracking autoradiography (PTA) analysis and transmission electron microscope (TEM) images of the samples showed that BN particles formed along prior austenite grain boundaries, and that as cooling rate increases, these particles become smaller and more numerous as shown Fig.2.57 [146]. This increase in the number of small BN precipitates may promote intergranular fracture, leading to a decrease in hot ductility in the lower austenite temperature region (900 to 1000 o C).…”
Section: Boronmentioning
confidence: 98%
See 1 more Smart Citation
“…It caused by the austenite/ ferrite transformation as discussed below. Cho et al 21,22) reported that the thickness of intergranular ferrite was the main reason which has great influences on hot ductility at the austenite and ferrite two-phase region. Generally, the strainstress curves obtained from hot tensile experiment are not ideal for studying the DRX due to the occurrence of necking.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the second phases precipitate more faster if the components with higher diffusion coefficient. 21) Boron has greater diffusion coefficient than other alloying elements. For example, the diffusion coefficient of boron in low carbon steel is on the order of 10 ¹10 m 2 /s at 1200°C in Fe, 24,25) and the diffusion coefficient of nitrogen is slightly less than that of boron.…”
Section: Influence Of Boron Addition On the Hot Ductility Of Low-carbmentioning
confidence: 99%